Autophagy Inhibitor (LY294002) and 5-fluorouracil (5-FU) Combination-Based Nanoliposome for Enhanced Efficacy Against Esophageal Squamous Cell Carcinoma - Ye Feng; Yongjian Gao; Dayu Wang; Zhonghang Xu; Weixuan Sun; Ping Ren (Nanoscale Research Letters, 2018)
Abstract In this study, 5-fluorouracil (5-FU) and LY294002 (LY)-loaded PEGylated nanoliposome was prepared to target esophageal squamous cell carcinoma (ESCC). The particles were characterized in terms of physicochemical and biological parameters. The co-delivery of autophagy inhibitor and chemotherapeutic drug in a single carrier was successfully accomplished. The two components from 5-FU and LY-loaded PEGylated nanoliposome (FLNP) released in a controlled manner with LY relatively released faster compared to that of 5-FU. FLNP showed a receptor-mediated cellular uptake that will allow the gradual release of drug in the acidic environment. The cellular uptake of nanoparticles (NP) was further confirmed by FACS analysis. The combination of 5-FU and LY resulted in higher cytotoxic effect compared to that of individual drugs. Most importantly, FLNP exhibited a significantly higher anticancer effect in cancer cells compared to that of free cocktail combinations. The faster release of LY from FLNP leads to autophagy inhibition that improves the sensitivity of cancer cells towards 5-FU, resulting in more cell death. Consistently, FLNP induced a greater apoptosis (~ 48%) of cancer cells compared to that of any other groups. Western blot analysis clearly showed that 5-FU and LY individually increased the expression of caspase-3 and PARP, while as expected FLNP induced a remarkable expression of these protein markers indicating the superior anticancer effect. We believe that the programmed release of autophagy inhibitor and chemotherapeutic drug from a single nanocarrier will increase the prospect of anticancer therapy in ESCC.